The senior high school students' perception on the use of Google Classroom in online English learning - Kurniawan, Heri; Suharjito, Bambang; Ariyanto, Sugeng (English Education Study Program, 2022)
This research was intended to describe the eleventh-grade students’ perception on the use of Google Classroom in online English learning at SMAN 1 Ngoro Mojokerto. Hence, this research used a descriptive research design because the objective of the study was to describe the students’ perception on the use of Google Classroom for online English learning during the pandemic. The data of this research were collected from the questionnaire. Further, the data of the research was calculated in the form of percentages and analyzed using quantitative analysis. The finding and discussion described the appropriateness of comfort, the content, efficient in use, language in Google Classroom application, clarity of the material, and fun to use. The result of the research showed that overall, the majority of the students had positive responses to every indicator and agreed that Google Classroom could facilitate them in an English classroom during pandemic situations. Keyword: Students’ Perception; Google Classroom; Online English learning